Perbedaan Tingkat Kematangan Karir Mahasiswa Ditinjau dari Masa Studi - Jalal, Novita Maulidya (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Career maturity is an important aspect in student development which reflects student readiness in making career decisions. This research aims to compare the career maturity level of psychology students based on the students' study period. This research uses a quantitative approach. The sample for this research consisted of 60 students from the Faculty of Psychology from three different study periods. Subjects were selected using the Accidental Sampling technique in each class. Data was collected using a career maturity scale, and analyzed using the Kruskall Wallis test. The research results show a significance value of 0.23 (Asymp.sig>0.05), which means there is no significant difference in the level of student career maturity in terms of their study period. The implication of this research is that career education interventions can help students develop career maturity in all their study periods.